Using multiple linear regression to assess the influencing factors towards online purchase intention of Sarawak layered cakes - Kenyang, Agnes Ayang; Hamdan, Anniza; Ali Hassan, Aimi Nuraida; Bujang, Noriham (Universiti Teknologi MARA, Perlis, 2025)
Nowadays, online purchases have become a major activity in shopping for goods and services. Following the changes in shopping activities brought about by the COVID-19 outbreak, several studies have investigated various factors influencing buyers' online purchase intentions. This study provides a comprehensive overview of the factors influencing the online purchase of Sarawak layered cake, a traditional delicacy from Sarawak. This study aims to investigate the impact of trust and safety, digital and social interactions, halal considerations, flexibility and conveniences on customer’s decisionmaking processes when purchasing Sarawak layered cake online. Primary data was collected through a Google Form questionnaire distributed to 51 respondents. Respondents’ experiences with or without online purchases of Sarawak layered cake were captured. The reliability analysis confirmed that the questionnaire was a reliable tool for measuring the study's objectives. Regression analysis revealed that all hypotheses were supported, with trust and safety as the most influential factors affecting attitudes and online purchase intentions for Sarawak layered cake. The findings obtained offers valuable insight for Sarawak layered cake producers and marketers to improve product offerings and refine marketing strategies. Furthermore, it can help improve customer preferences and satisfaction, as well as boost purchase intentions for Sarawak layered cake. In the future, stratified sampling could be employed to develop a more accurate prediction model for online purchase intentions of Sarawak layered cake in Malaysia.